Strategic Plan for a Coffee Company– Part 2 (British Journal of Multidisciplinary and Advanced Studies, 2025)
The purpose of this paper was to conduct a strategic plan of a Coffee Company in Durban, South Africa. The strategic plan strategies for growth were determined using the the SAFe criteria. The strategic plan included the McKinsey 7S model, the type of change being proposed and advise on sustainable strategy. The strategic opportunity identified for the Coffee Company was to diversify its products. In this regard, the recommendations to the Coffee Company focussed on product innovation. The recommendations were based on the 4R strategy of product diversification.